Macrophage activation in human diseases - Schultze, Joachim L.; Schmieder, Astrid; Goerdt, Sergij (Seminars in immunology, 2015)
It is becoming increasingly accepted that macrophages play a crucial role in many diseases associated with chronic inflammation, including atherosclerosis, obesity, diabetes, cancer, skin diseases, and even neurodegenerative diseases. It is therefore not surprising that macrophages in human diseases have gained significant interest during the last years. Molecular analysis combined with more sophisticated murine disease models and the application of genome-wide technologies has resulted in a much better understanding of the role of macrophages in human disease. We highlight important gain of knowledge during the last years for tumor-associated macrophages, and for macrophages in atherosclerosis, obesity and wound healing. Albeit these exciting findings certainly pave the way to novel diagnostics and therapeutics, several hurdles still need to be overcome. We propose a general outline for future research and development in disease-related macrophage biology based on integrating (1) genome-wide technologies, (2) direct human sampling, and (3) a dedicated use of in vivo model systems.
Gesehen am 19.02.2018